HUBUNGAN USIA MENIKAH DENGAN KEMAMPUAN IBU MERAWAT BAYI DAN BALITA DI WILAYAH KERJA PUSKESMAS PEMBUANG HULU KECAMATAN HANAU KABUPATEN SERUYAN - Mutiara R, Chatrine Indri; Dwi Salmarini, Desilestia; Mambang, Mambang (LPPM Universitas Sari Mulia, 2024)
Background: According to the United Nations Children's Fund (UNICEF) 1,220,900 girls in Indonesia were married before the age of 18. This figure places Indonesia among the 10 countries with the largest number of child marriages in the world. Objective: It is known that there is a relationship between early marriage and the ability of mothers to care for newborns in the Hanau sub-district. Methods: This study used a quantitative design with a cross-sectional approach, the number of samples used was 32 respondents, the measuring instrument used a questionnaire, with an ordinal measurement scale, the data obtained was processed using the Lambda correlation test.Result: The results of the study from 32 respondents to the sex of the baby were mostly female 59.4%, at the highest education level SMA 68.8%, children aged 1-12 months there were 37.5%. In the results, mothers <20 years have moderate ability to care for babies with a correlation of 0.024 p value <0.0005 which means (<0.05).Conclusion: In the study, the p value was 0.024 <0.05, which means that there is a relationship between the age of marriage and the ability of mothers to care for babies and toddlers, so it is recommended that among others it is expected to increase public awareness at the age of marriage because it will be difficult to care for their own babies because prospective mothers have not fully received Knowledge of proper baby care Keywords: Early Marriage, Baby Care, BBL